Genetic test for Mendelian fatigue and muscle weakness syndromes - Kiani, Aysha Karim; Amato, Bruno; Maitz, Silvia; Nodari, Savina; Benedetti, Sabrina; Agostini, Francesca; Lorusso, Lorenzo; Capelli, Enrica; Dautaj, Astrit; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Several inherited disorders involve chronic fatigue, muscle weakness and pain. These conditions can depend on muscle, nerve, brain, metabolic and mitochondrial defects. A major trigger of muscle weakness and fatigue is exercise. The amount of exercise that triggers symptoms and the frequency of symptoms are highly variable. In this review, the genetic causes and molecular pathways involved in these disorders are discussed along with the diagnostic and treatment options available, with the aim of fostering understanding of the disease and exploring therapeutic options.